ADAMTSL2 mutations determine the phenotypic severity in Geleophysic Dysplasia - Camarena, Vladimir (2024)
Geleophysic dysplasia-1 (GD1) is an autosomal recessive disorder caused by ADAMTS-like 2 (ADAMTSL2) variants. It is characterized by distinctive facial features, limited joint mobility, short stature, brachydactyly, and life-threatening cardiorespiratory complications. The clinical spectrum spans from perinatal lethality to milder adult phenotypes. We developed and characterized cellular and mouse models, to replicate the genetic profile of a patient who is compound heterozygous for 2 ADAMTSL2 variants, namely p.R61H and p.A165T. The impairment of ADAMTSL2 secretion was observed in both variants, but p.A165T exhibited a more severe impact. Mice carrying different allelic combinations revealed a spectrum of phenotypic severity, from lethality in knockout homozygotes to mild growth impairment observed in adult p.R61H homozygotes. Homozygous and hemizygous p.A165T mice survived but displayed severe respiratory and cardiac dysfunction. The respiratory dysfunction mainly affected the expiration phase, and some of these animals had microscopic post-obstructive pneumonia. Echocardiograms and MRI studies revealed a significant systolic dysfunction, accompanied by a reduction of the aortic root size. Histology verified the presence of hypertrophic cardiomyopathy with myocyte hypertrophy, chondroid metaplasia, and mild interstitial fibrosis. This study revealed a substantial correlation between the degree of impaired ADAMTSL2 secretion and the severity of the observed phenotype in GD1.